The Effect of the Combination of Different Methods of Stock Analysis on Portfolio Performance - Trančar Vesna (Naše gospodarstvo/Our economy, 2015)
The literature that examines the stock analysis is often faced with the same questions: Which stock analyses should be chosen and which indicators of individual stock analyses give the best information on whether a particular stock should be included in the portfolio? How many indicators and which combination of indicators should you choose to forecast future stock prices as accurately as possible? Can investors use stock analyses to create such a portfolio to meet the investment expectations? The main purpose of this article is to use theoretical methodology to determine whether the use of a combination of indicators from different stock analyses has a positive impact on the profitability of the portfolio.